Precision language education: a glimpse into a possible future - Lian, Andrew-Peter; Pannathon Sangarun, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This is a reflective article on “precision language education”. This concept is derived in part from “precision education” which, in turn, is derived from “precision medicine”. Precision language education heralds a new way of dealing with individual differences by effecting as precise a diagnosis as possible on each language learner, thus triggering specific interventions designed to target and respond to each person’s specific language-learning problems. The article develops the logic of precision language education, including the ways of eliciting and making visible, for both learner and observer, problems and difficulties to be diagnosed and remedied. It then briefly discusses the connection between personalized education and precision education before moving on to offer illustrative examples of precision language education at work which draw on a multiplicity of ways of addressing learning issues, including exploiting neuroplasticity. They include: an answer-evaluation and markup system, a phonetic correction system for three pairs of vowels and a neurological profiling system for guiding the forms of intervention applied. The article concludes with an argument that, in addition to offering a framework for action, precision language education enables the development of a flexible, coherent, “precision” mindset that is of benefit for generating individualized language learning systems to better meet the demands of the highly mobile, globalizing world of the 21st century.